Pricing and performance of IPOs: Evidence from Indian stock market - Iqbal Thonse Hawaldar; K.R. Naveen Kumar; T. Mallikarjunappa (Cogent Economics & Finance, 2018)
This study examines listing day performance of IPOs, book-built and fixed-price IPOs, post-listing aftermarket performance of IPOs, book-built and fixed-price IPOs in the Indian stock market. We examine pricing as well as long run performance of 464 (365 book-built IPOs and 99 fixed-price IPOs) Indian IPOs that went public between 2001 and 2011. The study covers 15 years from the financial year 2001 to 2015. Analysis of the results reveals that compared to fixed-price IPOs, book-built IPOs are underpriced by lesser magnitude. Moreover, book-built IPOs are associated with negative cumulative average abnormal returns (CAARs) up to five years and beyond, the negative CAARs associated with fixed-price IPOs turn positive after one and one-half year and continue to be positive thereafter.
Keywords: G10; G12; G32; 330; IPOs; underpricing; underperformance; book-building; fixed-price IPO